Filtering reality: Navigating Instagram’s influence on adolescent mental health - G Balamurugan; M Vijayarani (Journal of Education and Health Promotion)
The article presents a meticulous review of the multifaceted influence on the mental well-being of adolescents. This article focuses on how Instagram affects the mental health of teenagers. The researchers looked at databases like PubMed, PsycINFO, and Google Scholar for studies on “Instagram,” “adolescents,” “mental health,” “well-being,” “effect,” and “impact” from the year 2016-2023. They found 132 articles and chose 37 to study in depth. This study explores how Instagram affects teenagers’ mental health positively and negatively. On the positive side, Instagram can be a platform for creativity and connection. However, excessive use can lead to depression, anxiety, sleep problems, and low self-esteem. It also sheds light on the hidden danger of cyberbullying, which is rampant on Instagram and can severely impact adolescent mental well-being. While acknowledging these risks, the article recognizes that Instagram plays a role in adolescent socialization and offers opportunities for interventions, such as vaping awareness campaigns. The report wraps up by offering suggestions for handling teen mental health in the age of Instagram. Ideas include encouraging people to use Instagram responsibly, advising parents and instructors, and outlining areas for more research. The paper highlights the need for mindful technology use on Instagram because of its possible effects on teen mental health.